2008
DOI: 10.3310/hta12330
|View full text |Cite
|
Sign up to set email alerts
|

Performance of screening tests for child physical abuse in accident and emergency departments

Abstract: How to obtain copies of this and other HTA Programme reports. An electronic version of this publication, in Adobe Acrobat format, is available for downloading free of charge for personal use from the HTA website (www.hta.ac.uk). A fully searchable CD-ROM is also available (see below).Printed copies of HTA monographs cost £20 each (post and packing free in the UK) to both public and private sector purchasers from our Despatch Agents.Non-UK purchasers will have to pay a small fee for post and packing. For Europe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
73
1
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(78 citation statements)
references
References 210 publications
2
73
1
1
Order By: Relevance
“…A systematic review of the performance of screening tests concluded that adding a screening protocol to the clinical encounter yielded additional false-positives that exceeded additional abused children detected. 457 Compared with the general population, immigrant and refugee families may be more likely to suffer from the direct and indirect harms related to screening. Screening instruments have not been culturally validated and are less likely to be accurate because of factors such as language barriers, different cultural norms of behaviours and different attitudes toward institutional authority.…”
mentioning
confidence: 99%
“…A systematic review of the performance of screening tests concluded that adding a screening protocol to the clinical encounter yielded additional false-positives that exceeded additional abused children detected. 457 Compared with the general population, immigrant and refugee families may be more likely to suffer from the direct and indirect harms related to screening. Screening instruments have not been culturally validated and are less likely to be accurate because of factors such as language barriers, different cultural norms of behaviours and different attitudes toward institutional authority.…”
mentioning
confidence: 99%
“…Die zurückliegenden Jahre brachten eine Verschiebung des Auftrages von "Kinderschutz vor Gewalt" hin zu einem aktiven Schutzauftrag für eine sichere Umgebung und gesundes Aufwachsen (Barlow & Calam, 2011;Sethi et al, 2013;Munro et al, 2014: WHO, 2013 (Woodman et al, 2008. Vergleichbare Ergebnisse berichten Lee et al (2012), McKenzie et al (2011), Guenther et al (2009) und Newton et al (2010.…”
Section: Konsequenzen Und Entwicklungsmöglichkeitenunclassified
“…5 The low levels of recording in children aged ≥5 years contrast with evidence from community-based studies, which indicate higher rates of maltreatment in children of school age and adolescents. 5,15,37,38 Potential explanations include the fact that older children present less often to GPs, 3 GPs may fail to ask relevant questions, or they may recognise maltreatment but code it as something else.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
“…13,14 Evidence is lacking about how often GPs in England report child maltreatment. 15 National policy in the UK is starting to embrace evidence that child maltreatment occurs on continuums of severity and chronicity, and professionals often manage the problem without referral to child protection services. The government's response to the recent Munro Review of Child Protection recommended improved local coordination to identify children at risk of maltreatment who need early intervention but do not meet the criteria for receiving children's social care services.…”
Section: Introductionmentioning
confidence: 99%